Prawdziwe życia Vladimira Nabokova. Trzy (auto)biografie jednego autora = The real lives of Vladimir Nabokov. Three (auto)biographies of an author - Kotin, Andrej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The title of the article refers to Nabokov`s first English-language novel "The Real Life of Sebastian Knight", with a narrator who follows the trail of his recently deceased half-brother, an outstanding writer, to realize finally the futility of searching for objective truth about the artist and the human person in general. In addition to the mentioned text, the subject of analysis will also be Nabokov`s last completed novel "Look at the Harlequins!", in which the author`s life and work are revealed in the distorting mirror of literary fiction, and his autobiography "Speak, Memory", that can be seen as a kind of a "camouflaged" novel.
Keywords: Nabokov, Vladimir (1899-1977); autobiografia; fikcja literacka; autobiography; literary fiction